How do drivers recall positive and negative driving events? A quantitative approach to analysing driving diaries. (February 2020) - Barnard, M.P.; Pampel, S.; Burnett, G.; Allen, H.A.; Chapman, P.
Highlights: This study quantitatively analysed positive and negative driving diary events. Positive events were associated with control and a sense of reward. Negative events were associated with an increased use of function words. Results suggest a use of language that is reflective of appraisal frameworks. Abstract: Whilst diary studies are often analysed in a qualitative manner, quantitative methods which analyse the percentage of different types of language used in diary entries, now exist. From a driving perspective, this could arguably tell us more about the underlying psychological processes occurring when drivers reflect on their on-road experiences. As part of a larger project, the current study used a quantitative method of language analysis, known as word count analysis, to compare driver diaries in which positive and negative driving events were reflected upon. Results suggested that when describing positive events, drivers discuss them with more elaborate and descriptive language and focus on certainty and goal-driven processes. Negative events, however, had more of a social focus as indicated by an increased use of function words. These findings provide insights into the ways in which positive and negative driving events may be appraised. Additionally, drivers used more words indicating control and reward when describing positive driving events; this is discussed in consideration of how word count analyses can provide further insight into psychological process associated with emotion, such as appraisals.